Laboratory CO2 injection in Utrillas Sandstone (Cretaceous): Analysis of changes in porous media using Hg porosimetry - Campos, Rocío (My University, 2016)
CO2sc trapping and injection in non-exploitable saline aquifer pore spaces appears to be the most feasible method for reducing the emission of this greenhouse gas into the atmosphere. CO2sc trapping will be performed using four potential trapping mechanisms, as follows: (1) solubility trapping, (2) capillary trapping, (3) structural trapping, and (4) mineral trapping. The rock microstructure will play a key role in all the four mechanisms. This study has been conducted within the framework of the PmaCO2 project (Porosity and CO2 Trapping Mechanisms [1]).The goal of this study is to determine variations in pore space microstructure caused by the injection of CO2 in supercritical state in two samples of sandstone of almost identical chemical composition and different texture. We want to remark the key role of the initial rock texture in determining variations in the pore space and trapping mechanisms. These variations in pore space significantly affect the storage capacity of the rock and can modify the flow or percolation pattern of the fluid (or gas) through the rock. We analyzed rock response to the injection of CO2sc in two samples which chemical composition was analyzed in terms of major, minor and trace elements, and X-ray diffraction. Texture was analyzed using SEM imaging.
Keywords: Porosidad; Inyección CO2; Utrillas; PmaCO2